Scanning electron microscope observations on the multilocular disc-pores and dermal projections of adult female Porphyrophora tritici and P. cynodonti - Vahedi, Η.Α.; Gholami Mahfar, F. (ENTOMOLOGIA HELLENICA, 2010)
The morphology of the multilocular disc-pores from the anterior part of the body (abdominal segments I-III and all thoracic segments, dorso-venterally) of two species of Porphyrophora (P. tritici and P. cynodontis: Hemiptera: Coccoidea: Margarodidae) were examined using a scanning electron microscope. The multilocular disc-pores of both species have 1 or 2 (rarely 3) rings of evenly or unevenly distributed loculi but the more central rings are almost always incomplete. Each outer ring of the more anterior disc-pores of P. tritici was complete, with 5- 13 loculi, and the inner ring had 0-4 unevenly distributed loculi. Each disc-pore of P. cynodontis had a complete outer ring of 6-9 evenly distributed loculi and an inner ring with only 0-1 loculi. A bright central zone is absent in most cases. These two species are similar in that both have a dense network of small, globular projections throughout the derm surface. These observations are discussed in relation to those of light microscope studies.